Nocturnal Lagophthalmos in Pediatric Patient with Hydrocephalus: Poster Presentation - Case Report - Resident - IZZA ZUKHRUFIA; Yunia Irawati; Julie Dewi Barliana (Majalah Oftalmologi Indonesia, 2023)
Introduction : Nocturnal lagophthalmos is a physiologic and asymptomatic condition observed in 1.4-5% of the population. In unconscious patients, using mechanical ventilation and neuromuscular blocker medication can worsen the lagophthalmos, causing the patient to have exposure keratopathy. This report aims to emphasize the importance of eye care in unconscious patients. Case Illustration : A 5-year-old girl came with a chief complaint of a whitish lesion on the right eye. She got the lesion when hospitalized in Pediatric Intensive Care Unit for two weeks due to seizure attacks. A red and watery eye accompanied the whitish lesion. The patient had history of nocturnal lagophthalmos and Dandy-Walker syndrome, a complex malformation characterized by agenesis or hypoplasia of the vermis and cystic enlargement of the fourth ventricle. The corneal ulcer was treated with antibiotic treatment. After several visits, her infection had subsided but left a corneal cicatrix on her right eye. Discussion : In unconscious patients, it’s important to pay attention to the eyelid. Lagophthalmos can be divided into three groups; where grade 1 has complete eyelid closure; grade 2 has conjunctival exposure; and grade 3 has corneal exposure. It’s important to lubricate the eye in each grade and keep it closed using eyelid tape or cover in grades 2 and 3 to prevent exposure keratopathy. Surgical intervention can be considered when there is a risk of corneal ulcer. Conclusion : Prevention is always better than cure. Establishing standardized eye care in the intensive care unit is crucial to prevent ocular complications and preserve visual acuity.